Defect types and room temperature ferromagnetism in N-doped rutile TiO2 single crystals - 秦秀波 李东翔 李瑞琴 张鹏 李玉晓 王宝义 (中国物理B：英文版, 2014)
The magnetic properties and defect types of virgin and N-doped TiO2 single crystals are probed by superconducting quantum interference device （SQUID）, X-ray photoelectron spectroscopy （XPS）, and positron annihilation analysis （PAS）. Upon N doping, a twofold enhancement of the saturation magnetization is observed. Apparently, this enhancement is not related to an increase in oxygen vacancy, rather to unpaired 3d electrons in Ti3＋, arising from titanium vacancies and the replacement of O with N atoms in the futile structure. The production of titanium vacancies can enhance the room temperature ferromagnetism （RTFM）, and substitution of O with N is the onset of ferromagnetism by inducing relatively strong ferromagnetic ordering.